Endothelial Dysfunction: From Pathophysiology to Novel Therapeutic Approaches - Byeong Hwa Jeon (MDPI AG, 2021)
The vascular endothelium is an active tissue that plays a crucial role in the maintenance of vascular homeostasis [...]